2015
DOI: 10.1108/ejm-09-2013-0518
|View full text |Cite
|
Sign up to set email alerts
|

Consumer dominant value creation

Abstract: Abstract:Purpose: This paper discusses consumer driven value creation (value-in-use) across three different marketing logics: product dominant logic (PDL), service dominant logic (SDL) and consumer dominant logic (CDL). PDL conceptualises value as created by firms and delivered to consumers through products. SDL frames consumer value as a function of direct provider-consumer interaction, or consumer driven chains of action indirectly facilitated by the provider. Recently the research focus has been turning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…Whilst recently have scholars turned their attention over how value is co-created across various context-specific service environments (Vargo and Lusch 2016;Uhrich, 2014;Zagnoli and Radicchi, 2010;Anker et al, 2015) including music (Chaney, 2012;) sports (Woratschek et al, 2014;Stieler et al, 2014;Stieler et al, 2015), and the fine arts (Crossland, ), research has fallen short of capturing the unique nature of Fan Fests and the role of fans on value co-creation in such 'third' places of sport consumption. Our paper takes up this challenge and explores the still evolving nature of the Fan Fest.…”
Section: Exploring Value Co-creation In Fan Fests: the Role Of Fansmentioning
confidence: 99%
“…Whilst recently have scholars turned their attention over how value is co-created across various context-specific service environments (Vargo and Lusch 2016;Uhrich, 2014;Zagnoli and Radicchi, 2010;Anker et al, 2015) including music (Chaney, 2012;) sports (Woratschek et al, 2014;Stieler et al, 2014;Stieler et al, 2015), and the fine arts (Crossland, ), research has fallen short of capturing the unique nature of Fan Fests and the role of fans on value co-creation in such 'third' places of sport consumption. Our paper takes up this challenge and explores the still evolving nature of the Fan Fest.…”
Section: Exploring Value Co-creation In Fan Fests: the Role Of Fansmentioning
confidence: 99%
“…Service quality has been a recurrent, difficult, and expensive subject to maintain for most organizations. This finding is mainly because the market and the components that satisfy the customer (consumer) have evolved, and the demands are increasingly high (Anker et al, 2015;Chen, 2015;Grönroos & Gummerus, 2014). From the perspective of the theory of consumer behavior and service marketing, quality in the service has become a strategy that generates the following for a company: competitiveness, economic growth, market positioning, image, and reputation (Martínez & Martínez, 2010;Storbacka, Strandvik, & Grönroos, 1994;Suwandej, 2015).…”
Section: Quality In Service In the Image And Reputation Of The Companymentioning
confidence: 99%
“…Services are also conceived as economic activities whose result is not something physical or tangible but intangible and consumed simultaneously during its production (Kim, Tang, & Bosselman, 2018;Wallin Andreassenweight & Lindestad, 1998). Therefore, the generation of value is associated to the sensations of the customer-consumer at that moment, generating a value or not immediately (Anker, Sparks, Moutinho, & Grönroos, 2015;Goldstein, Johnston, Duffy, & Rao, 2002). The theory of consumer behavior has shown that customers in modern times have become more demanding and are assessing more precisely the elements that meet their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Egyes szerzők ezen irányzatra Product-dominant logic-ként (PDL) utalnak kutatásaikban (pl. Anker et al 2015;Baines et al 2013). Ez azonban csak terminológiai eltérést jelent, hiszen ugyanazon jelentést foglalja magában (Vargo-Lusch 2004;Veres 2012; Kelemen-Erdős 2015; Musová 2015).…”
Section: A Hagyományos (Gdl) Szemléletmódtól Az Sdl-igunclassified